Intercultural communication and miscommunication between Japanese and Vietnamese - Hoàng, Anh Thi (Đại học Quốc gia Hà Nội, 2020)
Therefore, to the Japanese, the Vietnamese’s positive to express themselves, can be consider to be pretentious, tob be warlike, to be undisciplined… in addition to discussing these feature of Japanese’s conscience about their group, this paper will describe the infulence of the concept “uchi-soto” on the usage of Japanese honorific language